Characterization of microRNA and Metabolite Profiles of Seminal Extracellular Vesicles in Boars - Jianfeng Ma (Animals, 2025)
Extracellular vesicles (EVs) contain bioactive substances and mediate a multitude of physiological functions. EVs can be found in most body fluids and are particularly abundant in semen. EVs have the potential to become a biomarker for the quality of boar semen. In this study, EVs were isolated from the semen of relatively young (10 months of age, Y-EVs) and old (30 months of age, O-EVs) duroc boars using ultracentrifugation. The isolated EVs were characterized using a transmission electron microscope, nanoparticle tracking analysis, and Western blotting. MicroRNA (miRNA) profiles and metabolomes were analyzed using high-throughput sequencing and liquid chromatography–mass spectrometry, respectively. The median particle sizes of Y-EVs and O-EVs were 151.3 nm and 162.1 nm, respectively. miR-148a-3p, miR-10b, miR-21-5p, miR-10a-5p, let-7a, etc., were identified as highly enriched miRNAs in seminal EVs of boars. Comparative analysis revealed 41 differentially expressed miRNAs and 132 differential metabolites between Y-EVs and O-EVs. Notably, 18 miRNAs were upregulated in O-EVs, such as miR-339-5p, miR-125a, miR-423-3p, and miR-29c, which were mainly enriched in endocytosis, focal adhesion, and adherens junction. KEGG pathway analysis further indicated that differential metabolites were enriched in glycerophospholipid metabolism. These results provide an insight into the functional roles of seminal EVs.